Participation and Duration of Environmental Agreements - Battaglini, Marco; Harstad, Bård (Journal of Political Economy, 2016)
We analyze participation in international environmental agreements in a dynamic game in which countries pollute and invest in green technologies. If complete contracts are feasible, participants eliminate the holdup problem associated with their investments; however, most countries prefer to free ride rather than participate. If investments are noncontractible, countries face a holdup problem every time they negotiate; but the free-rider problem can be mitigated and significant participation is feasible. Participation becomes attractive because only large coalitions commit to long-term agreements that circumvent the holdup problem. Under well-specified conditions even the first-best outcome is possible when the contract is incomplete.